GCN5L1 modulates cross-talk between mitochondria and cell signaling to regulate FoxO1 stability and gluconeogenesis - Lingdi Wang (Nature Portfolio, 2017)
Hepatic gluconeogenesis is tightly regulated at transcriptional level and is essential for survival during prolonged fasting. Here Wang et al. show that the mitochondrial enriched GCN5-like 1 protein controls hepatic glucose production by regulating FoxO1 protein levels via proteasome-dependent degradation and, in turn, gluconeogenic gene expression.